Effects of family involvement on the monitoring of CEO compensation - Sánchez Marín, Gregorio; Carrasco-Hernández, Antonio J. (My University, 2019)
This study examines the effectiveness of CEO compensation monitoring depending on the extent of family involvement in the firm. Considering the contradictory evidence on the effects of family involvement on CEO compensation reported by the literature to date, we adopt a procedural conception of CEO monitoring – that reflect processes and rules used in family firms for the alignment of CEO incentives structure to the firm interests –, to test four hypotheses derived from agency and socioemotional wealth (SEW) perspectives. Using a sample of 357 family and non-family Spanish companies, the results show that CEO compensation monitoring is inversely related to family status, and the relationship between CEO compensation monitoring and firm performance is stronger in firms where family influence is higher. In addition, we found that the presence of a family CEO negatively affects the implementation of economically instrumental monitoring mechanisms, decoupling CEO compensation from firm performance. Our research, aligned with recent socio-psychological literature on the study of processes of family firm’s management policies, thus contributes to a better understanding of the setting of CEO compensation in family firms as a result of a combination of common bonds and mutual expectations based on emotions and values with contractual and financial factors.